Zakat Requirement on Presidential Fund and Non-Zakat: A Detailed Examination of Scholars’ Opinions - Hafiz Liaqat Ali; Aziz ur Rehman Ariyan (jihat-ul-islam, 2023)
The government or the company deducts a certain amount from the salaries of its employees, voluntarily or forcibly, every month, in the name of Provident Fund, and adds the same amount to it and keeps it in its custody in the name of the employees. The money is paid to them on leaving the job, it is halal to take the whole amount, because half of it is from the employee himself and half is a reward from the government or the company. However, the research of the scholars regarding the obligation of zakat in the provident fund is that until the amount of the provident fund is received by the employee, zakat is not obligatory on him, and even after the money is received, the zakat of the previous years is not obligatory. However, the obligation of zakat on such money starts from the time when that money is received, except if the provident fund is not forced and the employee has deducted the money for it by his own authority, caution in this case. If the money is received, the previous year’s Zakat should be added.